2010
DOI: 10.29074/ascls.23.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii and MRSA Contamination on Reusable Phlebotomy Tourniquets

Abstract: DESIGN: Reusable tourniquets (n=200) were collected after being used for one day in the outpatient blood collection center (n=100) or during morning blood collection rounds on inpatient wards (n=100). Tourniquets were cultured and growth was screened for A. baumannii and S. aureus. A. baumannii isolates were identified using colonial morphology, oxidase, and GNI+ card on Vitek Legacy. S. aureus isolates were identified and screened for MRSA using colonial morphology, catalase, Staphaurex, and Oxacillin screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Healthcare‐associated acquisition of multi‐resistant organisms (MRO) including methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococcus (VRE) has been associated with increased nosocomial infections . Within the hospital environment, inanimate objects including inadequately disinfected blood pressure (BP) cuffs serve as reservoirs for MROs, resulting in the transmission of MROs to patients . Reducing potential reservoirs and acquisition of pathogens is thus a key measure in preventing nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare‐associated acquisition of multi‐resistant organisms (MRO) including methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococcus (VRE) has been associated with increased nosocomial infections . Within the hospital environment, inanimate objects including inadequately disinfected blood pressure (BP) cuffs serve as reservoirs for MROs, resulting in the transmission of MROs to patients . Reducing potential reservoirs and acquisition of pathogens is thus a key measure in preventing nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, the required frequency of cleaning is not specified, nor whether this would prevent transmission of MROs to patients. Previous studies have indicated varying rates of MRO colonisation of reusable tourniquets, and differ based on the sensitivity of the culture method used 17 . We performed this study to determine the prevalence of MRO colonisation of reusable venesection tourniquets in a Sydney teaching hospital using a sensitive enrichment method.…”
mentioning
confidence: 99%
“…The most important means of nosocomial spread is through carriage of S.aureus on the hands, scalp and anterior nares of healthcare workers [1]. However, fomites are being increasingly recognized as sources of nosocomial infections [2][3][4]. Disconcertingly high rates (81%) of MRSA in clinical specimens with S.aureus have been reported in Sri Lanka [5].…”
Section: Introductionmentioning
confidence: 99%
“…It also depends on the cleaning and infection control measures of the institution [6]. In other countries, phlebotomy tourniquets and faucets have been identified as important reservoirs of MRSA [2][3][4]6,7]. Although causality between contaminated tourniquets and increased MRSA infection has not been established, the potential for cross-contamination cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%